The beginning of ’Tsonga’ archaeology: excavations at Simunye, north-eastern Swaziland - Ohinata, F. (Southern African Humanities, 2002)
Tsonga-speakers comprise one of the four major linguistic groups in Africa south of the Limpopo (Van Warmelo 1974), but their cultural history has received little archaeological attention. This paper provides the first systematic description of ’Tsonga’ archaeology, resulting from a rescue excavation in 1999 of the Simunye site in north-eastern Swaziland. The Simunye site, which is dated to the latter half of the second millennium AD, produced ceramic material, an infant pot burial, a cluster of buried pots, glass trade beads, and other human and faunal remains, and was most likely inhabited by ancestors of Tsonga-speaking people.